Hypogammaglobulinemia in pediatric kidney transplant recipients. - Dimitriades, Victoria; Butani, Lavjay (Pediatric Nephrology, 2023)
Infections remain the most common cause of hospitalization after kidney transplantation, contributing to significant post-transplant morbidity and mortality. There is a growing body of literature that suggests that immunoglobulins may have a significant protective role against post-transplant infections, although the literature remains sparse, inconsistent, and not well publicized among pediatric nephrologists. Of great concern are data indicating a high prevalence of immunoglobulin abnormalities following transplantation and a possible link between these abnormalities and poorer outcomes. Our educational review focuses on the epidemiology and risk factors for the development of immunoglobulin abnormalities after kidney transplantation, the outcomes in patients with low immunoglobulin levels, and studies evaluating possible interventions to correct these immunoglobulin abnormalities.